2010
DOI: 10.1124/jpet.110.170688
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Induces Both Relaxations and Contractions, via Different α2-Adrenoceptor Subtypes, in the Isolated Mesenteric Artery and Aorta of the Rat

Abstract: Dexmedetomidine is an ␣ 2 -adrenoceptor agonist and anesthetic. The present study was designed to characterize the receptor subtypes and the downstream mechanisms of the vascular effects of dexmedetomidine in small (mesenteric artery) and large (aorta) arteries ex vivo. Isometric tension was measured in Sprague-Dawley rat mesenteric and aortic rings (with or without endothelium). To study relaxations, cumulative concentrations of dexmedetomidine, 5-bromo-N-(2-imidazolin-2-yl)-6-quinoxalinamine, (UK14304), or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 27 publications
(43 reference statements)
1
19
1
Order By: Relevance
“…Gi-protein, mediated by alpha2A-adrenergic receptors, and contraction was mediated by alpha2B and alpha1-adrenergic receptors and involved the action of prostanoids [67]. Furthermore, Porter et al showed that Dex increased actin cytoskeleton organization and inhibited isoproterenol-stimulated cAMP accumulation in the fetal rat heart.…”
Section: Discussionmentioning
confidence: 99%
“…Gi-protein, mediated by alpha2A-adrenergic receptors, and contraction was mediated by alpha2B and alpha1-adrenergic receptors and involved the action of prostanoids [67]. Furthermore, Porter et al showed that Dex increased actin cytoskeleton organization and inhibited isoproterenol-stimulated cAMP accumulation in the fetal rat heart.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on α 2 -adrenoceptor-mediated vascular smooth muscle contraction have employed isometric tension measurements on blood vessels, and the results have varied greatly depending on the luminal diameter of the vessel and its anatomical origin, with α 2 -adrenoceptors being more prominent in small arteries and veins but not in large arteries such as the aorta (Nielsen et al, 1989;Parkinson & Hughes, 1995;Roberts, 2001Roberts, , 2003. In particular, the vascular responses relating to dexmedetomidine appear to be very complex; in endotheliumdenuded arteries, the drug has induced contraction, whereas in intact vessels the relaxing and contracting effects of dexmedetomidine appear to oppose each other (Kim et al, 2009;Wong, Man, Vanhoutte, & Ng, 2010). In addition, dexmedetomidine has induced endotheliumdependent relaxation at low concentrations in contracted small arteries and contraction at higher concentrations (Wong et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…In particular, the vascular responses relating to dexmedetomidine appear to be very complex; in endotheliumdenuded arteries, the drug has induced contraction, whereas in intact vessels the relaxing and contracting effects of dexmedetomidine appear to oppose each other (Kim et al, 2009;Wong, Man, Vanhoutte, & Ng, 2010). In addition, dexmedetomidine has induced endotheliumdependent relaxation at low concentrations in contracted small arteries and contraction at higher concentrations (Wong et al, 2010). Studies on cultured vascular smooth muscle cells have been focused on the monitoring of intracellular calcium levels (Chotani et al, 2004;Hughes, Parkinson, & Wijetunge, 1996;Mironneau & Macrez-Lepretre, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Dexmedetomidine has α2:α1 binding selectivity ratio of 1620:1 compared to 220:1 for clonidine [5], and more predictable pharmacokinetic properties compared to clonidine [9,10]. It also possesses selective α2-adrenoceptor agonism, especially for the 2A subtype of this receptor, which causes it to be a much more effective sedative and analgesic agent than clonidine [11,12].…”
Section: Introductionmentioning
confidence: 99%